Contribution of the putative inner-pore region to the gating of the transient receptor potential vanilloid subtype 1 channel (TRPV1) - Susankova, Klara; Ettrich, Rudiger; Vyklicky, Ladislav; Teisinger, Jan; Vlachova, Viktorie (The Journal of neuroscience, 2007)
The transient receptor potential vanilloid receptor-1 (TRPV1) is a sensory neuron-specific nonselective cation channel that is gated in response to various noxious stimuli: pungent vanilloids, low pH, noxious heat, and depolarizing voltages. By its analogy to K+ channels, the S6 inner helix domain of TRPV1 (Y666-G683) is a prime candidate to form the most constricted region of the permeation pathway and might therefore encompass an as-yet-unmapped gate of the channel. Using alanine-scanning mutagenesis, we identified 16 of 17 residues, that when mutated affected the functionality of the TRPV1 channel with respect to at least one stimulus modality. T670A was the only substitution producing the wild-type channel phenotype, whereas Y666A and N676A were nonfunctional but present at the plasma membrane. The periodicity of the functional effects of mutations within the TRPV1 inner pore region is consistent with an alpha-helical structure in which T670 and A680 might play the roles of two bending "hinges."
Keywords: Alanine; TRPV Cation Channels; Ion Channel Gating; Membrane Potentials; Cell Line; mutace; kapsaicin; alanin; Electrophysiology; gating iontového kanálu; mutageneze cílená; membránové potenciály; krysa rodu Rattus; Mutagenesis, Site-Directed; Animals; elektrofyziologie; lidé; Capsaicin; Humans; zvířata; Rats; vysoká teplota; buněčné linie; Mutation; kationtové kanály TRPV; Hot Temperature